2022
DOI: 10.1152/advan.00045.2022
|View full text |Cite
|
Sign up to set email alerts
|

Physiology faculty and student contributions to schoolteacher training in neuroscience: innovations during the COVID-19 pandemic

Abstract: This study reports the experience of developing the ninth edition of the Neuroscience Applied to Education course in an online format that included synchronous and asynchronous activities. Here we show that schoolteachers consider the course important for acquiring new knowledge about neuroscience and the applicability of the concepts covered to improve their pedagogical practice and teaching environment. The online format did not prejudice the experience, and the technologies used were well evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Inclusion of neuroscience information has been found to be beneficial in several studies (e.g. Im et al, 2018;McMahon et al, 2019;Tadielo et al, 2022), reinforcing the finding that the presence of a neuroscientist as guest lecturer in the classroom adds legitimacy and substance to the information.…”
Section: Discussionmentioning
confidence: 67%
“…Inclusion of neuroscience information has been found to be beneficial in several studies (e.g. Im et al, 2018;McMahon et al, 2019;Tadielo et al, 2022), reinforcing the finding that the presence of a neuroscientist as guest lecturer in the classroom adds legitimacy and substance to the information.…”
Section: Discussionmentioning
confidence: 67%
“…This has negative repercussions on the initial training of future Andalusian teachers, since neuroeducation is a topic shown to be increasingly present in the future of society, according to previous studies [7][8][9][10][11][12][13][14][15][16][17]. To safeguard these training deficits, there are intervention programmes and training plans, with the aim of promoting knowledge about neuroscience and its applicability in education [6,[18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, changes were noted in the help offered, both in the student-teacher relationship and in classroom discipline. Trombini et al [21] conduct a five-week training course with 60 teachers in Brazil on neuroscience applied to education, with topics such as neuroanatomy, neurophysiology, neurobiology of learning and memory, neuroscience and education, etc. Teachers' perceptions after the training process indicated that the course was essential in the acquisition of new knowledge about neuroscience.…”
Section: Neuroeducation and Its Relevance To Teacher And Student Educ...mentioning
confidence: 99%